Dimensions and intensity of inter-professional teamwork in primary care: evidence from five international jurisdictions. (23rd October 2017) - Levesque, Jean-Frederic; Harris, Mark F; Scott, Cathie; Crabtree, Benjamin; Miller, William; Halma, Lisa M; Hogg, William E; Weenink, Jan-Willem; Advocat, Jenny R; Gunn, Jane; Russell, Grant
Abstract: Background: Inter-professional teamwork in primary care settings offers potential benefits for responding to the increasing complexity of patients' needs. While it is a central element in many reforms to primary care delivery, implementing inter-professional teamwork has proven to be more challenging than anticipated. Objective: The objective of this study was to better understand the dimensions and intensity of teamwork and the developmental process involved in creating fully integrated teams. Methods: Secondary analyses of qualitative and quantitative data from completed studies conducted in Australia, Canada and USA. Case studies and matrices were used, along with face-to-face group retreats, using a Collaborative Reflexive Deliberative Approach. Results: Four dimensions of teamwork were identified. The structural dimension relates to human resources and mechanisms implemented to create the foundations for teamwork. The operational dimension relates to the activities and programs conducted as part of the team's production of services. The relational dimension relates to the relationships and interactions occurring in the team. Finally, the functional dimension relates to definitions of roles and responsibilities aimed at coordinating the team's activities as well as to the shared vision, objectives and developmental activities aimed at ensuring the long-term cohesion of the team. There was a high degree of variation in the way the dimensions were addressed by reforms across the national contexts. Conclusion: The framework enables a clearer understanding of the incremental and iterative aspects that relate to higher achievement of teamwork. Future reforms of primary care need to address higher-level dimensions of teamwork to achieve its expected outcomes.